Influence Of Baby Massage (0-4 Months) Against Improvement Of Baby Weight - Fajriani, A.Tenri; Asmirati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2017)
Infant massage will stimulate the vagus nerve, the nerve where it will increase the intestinal peristalsis to empty stomach, the baby quickly so hungry that food intake will increase. This nerve also stimulates increased production of digestive enzymes, thus increasing the absorption of nutrients. Nutrients are absorbed will participate in blood circulation also increased by sympathetic nerve action potentials. This study aims to determine the effect of Infant Massage (0-4 Months) against Improved Weight Infants In Public Healt Bontobangung Quasi-experimental research type approach Non-Equivalent Control Group or non-randomized control group design. Samples were 30 people with purposive sampling technique sampling.The results were obtained using two independent samples t test obtained value Ï = 0.008 is smaller than Î± = 0.05 so that Ho refused and Ha accepted which means no effect of massage with baby's weight gain. Suggested health officials need to do counseling, demonstrations and distribution of leaflets so that mothers are motivated to do massage on the baby, this can be done through activities poyandu.